A ação social dos Bahá ís no Brasil - Paiva, Cirlei Izabel da Silva (2008)
This work brings the mainly theme the religion Bahá i, more specifically the social action of it in Brazil, with the objective to check which is the space that the Bahá i faith occupies in Brazilian society. To get this intention, our study based itself in first moment with Max Weber, Clifford Geertz, Peter Beger, looking for the understand of religious phenomenon and the vision of the world and of the ethos being feature of construction of religiously identity. In another moment, are present the ideas of Paulo Freire, Pablo Gentili, John Dewey, Álvaro Vieira Pinto, glimpsing a reflection about the education questions that based the social action of the Bahá i faith. Using the qualitative quotation of research, being used collected data in document analyze Interviews, participative observation, besides of bibliographic research. The results of the research indicated that the space occupied by Bahá i faith is the one of Education, that, according to the principles Bahí I formed itself in the possibility of transformation of social behavior and the construction of a world more harmonious, that prevails the unit of human gender